Rol del sistema financiero en los procesos de centralización del capital del cantón Macara. - INGA GUALÁN, JESSICA ALEXANDRA (2012)
The present investigative work makes reference to the ROLE OF FINANCIAL SYSTEMS IN THE PROCESS OF CENTRALIZATION OF CAPITAL OF THE CANTON MACARA, highlighting the impact that the financial institutions have in each of the different sectors of the canton. With the obtained results, we can determine that there is a market capitalization of the territory, given that an average financial system performed more loans that deposits, which wants us to say that the financial system contributes to the economic and productive development of the canton. The financial institutions also offer his services to nearby cantons, these organizations does not count on autonomy, to if also the agency heads they lack faculty to make decisions that is to say, depend on the respective matrix, which entails to that the customers wait major time for the moment to realize a procedure, the permanency on the market of the financial institutions depends largely of the number of clients with whom they count, considered that the financial market becomes ever more competitive day between each of the agencies, these independently present, major profitability, solvency and safety is so they possess an important market share. Regarding the managerial system, the canton Macara is an eminently commercial town, and which business system years ago there was growing as the one currently taking this was mainly due to lack of knowledge of business administration, Because they were constituted as family businesses, where they were and are managed by one of the spouses, the same as in most cases, were not enabled. It is so it exists relations of affinity as of consanguinity between companies, due to the fact that the managerial sector is in hands of a limited group of inhabitants, already be on the shareholding part, where there exist inhabitants who possess several business with different lines of products or services to offering; as well as the administrative part, which is carried out by the owners. By means of the results obtained so much of the financial as managerial structure, we can emphasize that a similarity exists between these sectors, through financial market invigorates the economy, allowing the managerial development of the canton, the financial system has great reception, because of the studied companies one of them has realized a credit which the financial system has demonstrated solvency and capacity, in addition to grant the appropriations of agile and opportune form in relation with other not regular financial institutions, promoting this way the development of the canton and satisfying the needs of his clients. Fomenting therefore the development of the canton and satisfying the needs of their customers.